Fiqh Polygamy in the Context of Social Change: A Crisis Study on the Adaptation of Islamic Law and the Response of Modern Society - Az-Zahra’ Musthofifi (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study explores the fiqh of polygamy in the context of social change, highlighting the adaptation of Islamic law and the response of modern society. This research aims to understand how fiqh laws on polygamy are translated and applied in the ever-evolving social dynamics and how modern society responds to these norms. Theoretical Framework: The theoretical framework of this study refers to the concepts of ijtihad and maqashid shariah, emphasizing the flexibility of Islamic law in dealing with social changes. Additionally, social theories on modernization and globalization are used to analyze shifts in societal views on polygamy. Literature Review: A review of the literature indicates that polygamy has long been part of Islamic law, with various interpretations across different fiqh schools. However, in the modern context, there are significant differences in its implementation across Muslim-majority countries, influenced by legal regulations, gender awareness, and human rights values. Methods: This research employs a qualitative method with a case study approach. Data were collected through interviews with scholars, academics, and practitioners of Islamic law, as well as surveys of Muslim communities in several countries with diverse Muslim populations. Thematic data analysis was conducted to identify key patterns in the application and acceptance of polygamy. Results: The study's findings reveal significant variations in the implementation of polygamy, ranging from full acceptance to rejection or adjustment to a broader social context. Factors such as education levels, awareness of women's rights, and the influence of globalization play a crucial role in shaping societal views and practices regarding polygamy. Implications: The implications of this research emphasize the importance of reform and adaptation in fiqh laws on polygamy to remain relevant to social developments. Legal adjustments are necessary to maintain a balance between religious principles and contemporary societal needs without disregarding the essence of shariah. Novelty: The novelty of this research lies in its comprehensive analysis of modern society's response to polygamy in the context of social change, as well as its interdisciplinary approach that integrates Islamic legal perspectives with social theories. The findings are expected to provide deeper insights into the challenges and solutions in managing Islamic family law in the modern era.